Ammonia inhalation for enhancing physical performance and exercise tolerance in physically active individuals and athletes: a systematic review - Eduard Bezuglov; Evgeniy Achkasov; Timur Vakhidov; Elizaveta Kapralova; Georgiy Malyakin; Evgeniy Lebedenko; Vladimir Frolov; Mikhail Butovskiy; Omid Etemad Arroyo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Ammonia inhalation (AI) has gained popularity among differing athletic populations and physically active individuals. However, studies have investigated the effect of AI on various aspects of physical performance and exercise tolerance and reported contradictory findings.